Heterologous prime-boost BCG with DNA vaccine expressing fusion antigens Rv2299c and Ag85A improves protective efficacy against Mycobacterium tuberculosis in mice - Wu, Juan; Hu, Zhidong; Lu, Shui-Hua; Fan, Xiao-Yong (Frontiers in Microbiology, 2022)
The development of heterologous prime-boost regimens utilizing Bacille Calmette–Guerin (BCG) as the priming vaccine is a promising approach to improve the efficacy of vaccination against tuberculosis (TB). In this study, we examined the ability of a DNA vaccine that expressed a fusion of antigens Rv2299c and Ag85A to boost BCG immunity and protection against Mycobacterium tuberculosis (Mtb) in Balb/c mice. The fusion DNA vaccine was moderately immunogenic and afforded some protection when used on its own. After a priming BCG vaccination, the DNA boost significantly amplified Th1-type cell-mediated immunity compared to that resulting from either BCG or DNA immunization. In the DNA-boosted mice, Ag-specific CD4+ and CD8+ T cells that were mono-positive for IFN-γ alone were the most prominently expanded in infected lungs. The protective efficacy afforded by BCG against challenge infection was greatly improved by the DNA boost; bacterial loads were significantly reduced in both spleen and lung and histological damage in the lung was less. The use of a DNA vaccine containing the fusion antigens Rv2299c and Ag85A to boost BCG may be a good choice for the rational design of an efficient vaccination strategy against TB.